(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: Hashimoto thyroiditis is an autoimmune disease in which thyroid cells are destroyed by both cell mediated and antibody mediated processes. It is the most common cause of hypothyroidism in iodine sufficient areas with an incidence of 0.3 -1.5 /1000 per year. During the histopathological evaluation of HT, thyroid neoplasms including papillary thyroid carcinoma(PTC) are detected incidentally which is currently one of the primary area of research in thyroid pathology . This study aimed to explore the role of histopathological study along with its correlation with clinical presentation ,biochemical and radiological parameters in the diagnosis of HT. Methods: This was a retrospective study conducted in a tertiary care hospital over a period of 5 years from June 2019 to June 2024.A total of 45 cases of thyroidectomy specimens were included in the study. All the thyroidectomy specimens which showed only features of Hashimoto thyroiditis on histopathological as the only pathology were included in the study. All the relevant clinical information ,radiological findings of thyroid gland, thyroid hormone assay and thyroid autoantibody studies were collected from the clinical records of the patients and analysed statistically. Result: In our study ,most of the cases belonged to the 31-40 years age group. Females were more affected than males. Majority of the patients presented with midline neck swelling and diffuse thyroid enlargement without nodularity. Autoantibody titre showed presence of antithyroglobulin antibodies anti-TPO antibodies in almost all cases .On microscopic examination of the thyroidectomy specimens, the most common finding were hurthle cell change and lymphoid follicles which were present in all cases . Conclusion: majority of Hashimoto thyroiditis patients run a benign clinical course but in minor percentage of cases there is increased risk of development of malignancies particularly papillary thyroid carcinoma. Close follow up of these patients can lead to early diagnosis and prompt treatment for better management of the patients.